Identifikasi Kegagalan Mesin CNC JOBS LINX 30 COMPACT menggunakan Metode Root Cause Analysis dan Failure Mode and Effect Analysis - Shintha Lailatul Maghfiroh; Anda Iviana Juniani; Nurvita Arumsari (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
CNC JOBS LINX 30 COMPACT is used to produce many aircraft components in one company engaged in manufacturing in Indonesia. This machine works by giving a command signal (a program) to reduce the dimensions of the product vertically and horisontally according to the program. In order to satisfy aboaut demand, so be required machine operation condition which reliable. To determine whether the machine is reliable or not, it is necessary to identify the failure of the machine during the operation of the machine. Identification of failure is done by finding the root cause of failure using Root Cause Analysis method, and look for critical components of the machine using FMEA (Failure Mode and Effect Analysis) method.